Défis et responsabilités suite à la déclaration de la diète méditerranéenne comme patrimoine culturel immatériel de l’humanité (Unesco) - Isabel González Turmo; François-Xavier Medina (Revue d'ethnoécologie)
UNESCO declared the Mediterranean Diet as Intangible Cultural Heritage of Humanity in November 2010. But this heritage was not proposed as a nutritional model or even as an opportunity to develop a range of healthy foods. It was much more than that, because it was related to techniques, practices, habits, ideas, values and food spaces. The Mediterranean diet was threatened and its safeguard was urgent. However, since its approval we do not hear yet about the heritage values of the Mediterranean diet. In this article we will take a critical reflection on the present and the future of the Mediterranean Diet as Intangible Cultural Heritage.